ANALISIS CONTRACT CHANGE ORDER PADA PELAKSANAAN PROYEK APARTEMEN ALTON SEMARANG - Muhammad Abdul Khalim; Henny Pratiwi Adi; Abdul Rochim (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
A contract change order (CCO) is a job change activity in a construction project that is carried out during the work implementation period. This study aims to determine the factors that cause contract change orders, analyze the impact given if there is a contract change order and analyze what strategies must be done to resolve the occurrence of contract change orders in the implementation of the Alton Apartment building construction project located in the city of Semarang. The data collected in this study used a semi-structured interview method with competent sources in their field, while the sources for data collection were construction management consultants (MK), contractors & owners. The Strength, Weakness, Opportunity, Threats (SWOT) analysis method is used to determine the right strategy to deal with CCO activities. The conclusion of the study, CCO was caused by an imperfect design that resulted in the achievement of time and costs not being on target, the strategy was obtained by accelerating work, controlling each work and project cashflow and referring back to the wholesale contract that was mutually agreed upon in the event of a dispute.